2020
DOI: 10.3390/nu12123839
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Interventions to Improve Asthma-Related Outcomes through Immunomodulation: A Systematic Review

Abstract: Asthma is a chronic inflammatory disease of the airways, characterized by T-helper (Th) 2 inflammation. Current lifestyle recommendations for asthma patients are to consume a diet high in fruits and vegetables and to maintain a healthy weight. This raises the question of whether other nutritional interventions may also improve asthma-related outcomes and whether these changes occur via immunomodulation. Therefore, we systematically reviewed studies that reported both asthma-related outcomes as well as immunolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 83 publications
0
20
0
1
Order By: Relevance
“…Also, van Brakel et al performed a systematic review involving 30 articles describing 28 individual studies clustered based on six nutritional interventions -herbs, herbal mixtures and extracts, supplements, weightloss, vitamin D, and Omega-3 LCPUFAs. They found no improvement in lung function in four out of five studies from the vitamin D3 supplementation cluster while none of the studies recorded an improvement in asthma control or quality of life with vitamin D supplements [2]. In the metanalysis involving seven randomized controlled trials by Luo et al where four studies were in adults, the researchers found no improvement in asthma exacerbation following supplementation with vitamin D; the study findings were, however, based on a statistical analysis of the data from all the seven studies reviewed [5].…”
Section: Effect Of Vitamin D Supplementation On Asthma Exacerbation In Adultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Also, van Brakel et al performed a systematic review involving 30 articles describing 28 individual studies clustered based on six nutritional interventions -herbs, herbal mixtures and extracts, supplements, weightloss, vitamin D, and Omega-3 LCPUFAs. They found no improvement in lung function in four out of five studies from the vitamin D3 supplementation cluster while none of the studies recorded an improvement in asthma control or quality of life with vitamin D supplements [2]. In the metanalysis involving seven randomized controlled trials by Luo et al where four studies were in adults, the researchers found no improvement in asthma exacerbation following supplementation with vitamin D; the study findings were, however, based on a statistical analysis of the data from all the seven studies reviewed [5].…”
Section: Effect Of Vitamin D Supplementation On Asthma Exacerbation In Adultsmentioning
confidence: 97%
“…The lethality associated with asthma exacerbations highlights the importance of studying asthma and conditions limiting its flare-up [5]. Chronic inflammation from asthma modulated by immune cells, T-helper (Th) cells, leads to activation of mast cell and immunoglobulin E (IgE) and contribute to further inflammation of the airways, creating wheezing, chest tightness, and cough symptoms [2].…”
Section: Figure 1: Triggers Of Asthma Exacerbationmentioning
confidence: 99%
See 2 more Smart Citations
“…The most recent systematic review, by van Brakel et al 94 found five studies, of which none reported positive associations with lung function or asthma control. 94 The studies using New Zealand green-lipped mussel extracts were most effective-were able to reduce FeNO 95 and exhaled H 2 O 2c . 96 Interestingly, the studies with the lowest doses seemed more effective.…”
Section: Adult Intake Of Fatty Acids To Prevent And/or Manage Asthmamentioning
confidence: 99%